Poverty, Mental Health, and Counsellors for Social Justice: Reflections on an Interactive Workshop - Audet, Cristelle; Collins, Sandra; Jay, Melissa; Irvine, Kathleen; Hill-Lehr, Andria; Schmolke, Christina (Canadian Journal of Counselling and Psychotherapy, 2014)
Poverty is a hidden yet pervasive reality affecting the health of many Canadians. Counsellors may not fully grasp the impacts of poverty because of their social and economic privilege. This article summarizes an interactive workshop offered by the Social Justice Chapter at the 2010 conference of the Canadian Counselling and Psychotherapy Association. Its purpose is to (a) raise consciousness about Canada’s poor track record in ensuring basic supports for mental and physical well-being of all people and about the impact of poverty on mental health, (b) bring to life the experiences of those living at or below poverty levels, (c) examine the impact of poverty on counselling practice in Canada, and (d) generate momentum for exploring systems-level interventions designed to address these needs.